Plan de Marketing para la Empresa “Librería Academia” en la Ciudad de Loja - Armijos Herrera, Esperanza del Cisne (2016)
The research is oriented to the elaboration of a Marketing Plan for the company "LIBRERÍA ACADEMIA" in the city of Loja, that will lead to the development and growth of the same. The general objective of the present project is to elaborate a marketing plan for the "LIBRARY" ACADEMY of the city of Loja; To maintain an acceptable level of competitiveness. For the development, a theoretical framework was elaborated in which all the foundations of each one of the aspects treated in the investigation are elaborated, also it was necessary of the aid of a methodology that allowed to maintain a sequence and order in each aspect treated to carry out the analyzes : External, competitive and internal, and market research through techniques and instruments for data collection, such as the interview guide that was applied to managers and staff of the company; General manager, chief financial officer and sales manager, we also used the questionnaire that was applied to the clients of the company and with the results we could perform the analysis and interpretation of the same. The results show the interpretation of each PESTEC analysis, study of the political, economic, social, technological and environmental factors, allowing to find key information for the company, these results found were located in the MEFE matrix that results Weighted a value of 2.68 which means the company has more opportunities than threats. The competitive analysis allowed to know the main direct rivals, such as the Aguilar bookstore occupying a position of 2.60 followed in positioning in the market by the bookstore Ecuador in a position of 2.15, in the third place the bookstore Palacios with a position of 1.80, and lastly The San José bookstore with the 1.75 that leaves in the fourth place. When performing the internal analysis, each of the most important marketing variables was investigated to generate an interview guide and applied to the key members of the company. This information was located in the MEFI matrix, which results in a weighted result of 3.56 indicating That the organization is slightly stronger than weak, where strengths weigh more as good market share, well defined market segment, and weaknesses weigh less such as customer disloyalty, lack of promotions and lack of staff training . Then the market research was carried out to identify and solve the various problems that the company may be experiencing. Based on all the analyzes carried out, the proposal of a marketing plan is drawn up with the purpose of leading the company towards improvement, which contains strategic objectives, for which it has established the appropriate strategies, goals , Actions, responsible and budget of the proposed objectives. Finally, after the studies carried out, it has been concluded that the bookstore does not have advertising or promotions with which to attract more buyers, also that sellers are not being properly trained to serve customers, in addition to the imposition of taxes and tariff measures In the current year has affected the company in its economy.